2019
DOI: 10.1097/pcc.0000000000001783
|View full text |Cite
|
Sign up to set email alerts
|

Positive Airway Pressure Versus High-Flow Nasal Cannula for Prevention of Extubation Failure in Infants After Congenital Heart Surgery*

Abstract: Objectives: Compare the impact of initial extubation to positive airway pressure versus high-flow nasal cannula on postoperative outcomes in neonates and infants after congenital heart surgery. Design: Retrospective cohort study with propensity-matched analysis. Setting: Cardiac ICU within a tertiary care children’s hospital. Patients: Patients less than 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The pre‐ and post‐implementation study designs of the quoted studies suggest that temporal changes in care delivery, such as implementing a standardised extubation process in our study, may explain differences in reintubation rates. Other paediatric studies have shown no difference in extubation failure rates for preterm infants 29 or infants after cardiac surgery 30 who received HFNT or CPAP for post‐extubation respiratory failure. Together, these data suggest that HFNT and CPAP may provide comparable support for post‐extubation respiratory failure.…”
Section: Discussionmentioning
confidence: 94%
“…The pre‐ and post‐implementation study designs of the quoted studies suggest that temporal changes in care delivery, such as implementing a standardised extubation process in our study, may explain differences in reintubation rates. Other paediatric studies have shown no difference in extubation failure rates for preterm infants 29 or infants after cardiac surgery 30 who received HFNT or CPAP for post‐extubation respiratory failure. Together, these data suggest that HFNT and CPAP may provide comparable support for post‐extubation respiratory failure.…”
Section: Discussionmentioning
confidence: 94%
“…Extubation failure after congenital heart surgery is associated with prolonged hospital stay and mortality [23]. Studies have shown that BiPAP could reduce the need for reintubation, especially in patients with respiratory failure and cardiogenic pulmonary edema [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Schibler et al conducted a retrospective analysis in all infants admitted to PICU, requiring HFNC between 2005 and 2009, showed an overall reduction in the intubation rate to 7% compared to their local registry [9]. When comparing HFNC to noninvasive ventilation in post extubated infants who underwent congenital heart surgery, there was no statistical difference in the reintubation rate [40]. In adults, a multicenter randomized control trial was conducted in adult patients admitted to ICU with hypoxic respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…It compared the rate of intubation among patients receiving conventional oxygen therapy, HFNC, and NIV. It showed no significant difference in the outcome, but showed significant 90 days mortality reduction in the group treated with HFNC [40]. A meta-analysis done by Zhao, H et al comparing HFNC with conventional oxygen therapy and NIV, showed that HFNC is associated with a reduction in intubation rate when compared to conventional oxygen therapy (COT) but not to noninvasive ventilation (NIV) [41].…”
Section: Discussionmentioning
confidence: 99%